2014
DOI: 10.1186/ar4603
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic benefit of balneotherapy and hydrotherapy in the management of fibromyalgia syndrome: a qualitative systematic review and meta-analysis of randomized controlled trials

Abstract: IntroductionIn the present systematic review and meta-analysis, we assessed the effectiveness of different forms of balneotherapy (BT) and hydrotherapy (HT) in the management of fibromyalgia syndrome (FMS).MethodsA systematic literature search was conducted through April 2013 (Medline via Pubmed, Cochrane Central Register of Controlled Trials, EMBASE, and CAMBASE). Standardized mean differences (SMDs) and 95% confidence intervals (CIs) were calculated using a random-effects model.ResultsMeta-analysis showed mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 78 publications
3
54
2
1
Order By: Relevance
“…There was a significant improvement in pain (−0.78; −1.42 to −0.13) at the end of therapy, maintained in the longer term (median 14 weeks), although the review authors noted that no trials conducted an ITT analysis. There was consistency with regard to the evidence for hydrotherapy and balneotherapy, although little evidence to suggest superiority of one over the other 77 . Hydrotherapy evaluation: weak for (93% agreement) .…”
Section: Resultsmentioning
confidence: 92%
“…There was a significant improvement in pain (−0.78; −1.42 to −0.13) at the end of therapy, maintained in the longer term (median 14 weeks), although the review authors noted that no trials conducted an ITT analysis. There was consistency with regard to the evidence for hydrotherapy and balneotherapy, although little evidence to suggest superiority of one over the other 77 . Hydrotherapy evaluation: weak for (93% agreement) .…”
Section: Resultsmentioning
confidence: 92%
“…36 A systematic review and meta-analysis of 8 RCTs (overall N = 462) of the therapeutic benefit of hydrotherapy (water treatments) for FM provided moderate-to-strong evidence for a small improvement in HRQoL at the end of treatment, but not in depression or tender-point count. 37 Five RCTs (overall N = 177) of balneotherapy (spa treatments in mineral/thermal water) produced moderate evidence for a moderate-to-large reduction in pain and tender-point count at the end of treatment; a smaller effect on pain was maintained at follow-up.…”
Section: Other Cam Therapiesmentioning
confidence: 96%
“…Various other scientific studies, mainly in people with fibromyalgia [19,20], osteoarthritis [21][22][23][24][25][26][27][28][29][30], chronic low back pain [31,32] and chronic venous insufficiency [33,34], have found that balneotherapy and undergoing such treatments resulted in an improved quality of life in regard to health.…”
Section: Discussionmentioning
confidence: 99%